Skin care services and disease prevalence in Taiwan: A nationwide study - Ying-Xiu Dai; Tzeng-Ji Chen; Yun-Ting Chang (Wolters Kluwer Medknow Publications, 2018)
Background/Objective: Numerous studies have suggested that dermatologists are superior to nondermatologists in managing skin diseases. However, it is still not known whether the public are convinced that dermatologists should be the primary caretakers for the skin. This study sought to characterize the delivery of skin care services, with a particular focus on the epidemiology of skin diseases and the distributions of patients and their visits to dermatologists and nondermatologists. Methods: The cohort datasets were drawn from Taiwan's National Health Insurance Research Database (NHIRD) and contained all the original claims data for one million beneficiaries enrolled in 2010. We analyzed the epidemiologic profiles of this population-based cohort for 2013. Descriptive statistics were applied to examine the epidemiology of skin diseases and the distributions of visits and patients according to physician specialty. Results: We identified 989,039 persons who remained in the cohort in 2013. Of those, 351,330 (or 35.5%) had skin diseases, and made 989,514 ambulatory care visits in 2013. Visits to dermatologists accounted for 62.2% of these visits. Among the patients with skin diseases, 52.6% of patients made visits to dermatologists, compared with 32.6% who visited nondermatologists and 14.8% who visited both in 2013. In this cohort, dermatitis and eczema had the highest prevalence (16.2%), followed by fungal infections (6.3%) and pruritus (5.5%). Conclusion: Dermatologists play major roles in providing skin care services in Taiwan. This finding might be partially explained by the weak role of primary care physicians and the perceptions of patients toward dermatologists and nondermatologists in Taiwan. Keywords: Healthcare utilization, Skin diseases, Epidemiology, Taiwan